Prevalence and Treatment Patterns of Sleep Disorders in the Under 20 Population: analysis using a national health insurance claims database - Jang Won Lee; Jinseub Hwang; Min Kyung Hyun (Korean Pharmacopuncture Institute, 2022)
Objectives: Child and adolescent sleep is an important factor for brain and physical development. Therefore, it is necessary to investigate the prevalence of sleep disorders and nonorganic sleep disorders in children and adolescents and determine the type of utilization of medical institutions. This study analyzed the prevalence and type of medical institutions in Korean children and adolescents with sleep disorders and nonorganic sleep disorders.Methods : This study used data recorded in the Health Insurance Review and Assessment- National Patient Sample (HIRA-NPS) database from 2010 to 2017. Details of medical institution type and patient's sex, age, and treatment type were extracted for patients younger than 20 years with sleep disorders and nonorganic sleep disorders.Results : Among 2,536,478 patients under age 20, we identified 3,772 patients with sleep disorders or nonorganic sleep disorders. From 2010 to 2017, the prevalence of sleep disorders in children and adolescents was 0.07% to 0.09%. The utilization rate of Korean medical institutions was 30.47%. The prevalence of nonorganic sleep disorders and the utilization rate of Korean medical institutions were 0.06% to 0.08% and 45.99%, respectively.Conclusion : The prevalence of sleep disorders and nonorganic sleep disorders in the under- 20 population was 0.14% to 0.16%. More than 70% of patients with nonorganic sleep disorder who were younger than 9 years used Korean medical institutions.